The Effectiveness of Student Assistance Program (PROAES) of the Federal University of Espírito Santo for reduction of evasion of indices of undergraduate students - Lima Azevedo, Simone (Guará Journal, 2017)
This paper investigates the performance of the Student Assistance Program, Federal University of Espírito Santo (UFES) for the retention of low-income students at the university, with reduced percentages of avoidance, comparing numbers and dropout rates between the two school years preceding the adoption of student assistance policy (2010 and 2011 ) with two subsequent school years (2012 and 2013). And as a theoretical framework, this paper discusses existing forms of evasion in college, rescues a brief history of evasion in higher education in the country and the main theoretical models on the topic, and shows the number of avoidance by teaching center and by type in UFES as a way to identify, although superficially, the profile of evaded student/ retained. Investigates the policies adopted to curb evasion in this university, and relates the reduction, if any, of this index with the policies of student assistance.